Talimogene laherparepvec: First in class oncolytic virotherapy - Conry, Robert M.; Westbrook, Brian; McKee, Svetlana; Norwood, Timothy Graham (Human vaccines & immunotherapeutics, 2018)
Oncolytic viruses represent a novel drug class in which native or modified viruses mediate tumor regression through selective replication within and lysis of tumor cells as well as induction of systemic antitumor immunity capable of eradicating tumor at distant, uninjected sites. Talimogene laherparepvec (TVEC) is a type I herpes simplex virus genetically modified to preferentially replicate in tumor cells, enhance antigen loading of MHC class I molecules and express granulocyte-macrophage colony-stimulating factor to increase tumor-antigen presentation by dendritic cells. It is presently the only oncolytic virus approved by the FDA with an indication for advanced melanoma based upon improved durable response rate in a randomized, phase III trial. Clinical trials are underway in melanoma investigating TVEC as neoadjuvant monotherapy and in combination with checkpoint inhibitors for unresectable disease as well as in an array of other malignancies. It is appropriate to review TVEC's biology mechanism of action, clinical indication and future directions as a prototype of the burgeoning class of oncolytic viruses.